Presence of Daphnia (Ctenodaphnia) menucoensis Paggi, 1996 in La Pampa Province (Argentina) (Semiárida, 2020)
We report the presence of Daphnia (Ctenodaphnia) menucoensis Paggi, 1996, in three saline ponds of La Pampa Province (Argentina). This work confirms that the species is distributed along the arid and semiarid stripe that extends from the central region of Argentina to the Patagonian plateau.
Keywords: Cladocera; Daphnia; Ctenodsphnia